PENGARUH PENYULUHAN HIV/AIDS TERHADAP PENGETAHUAN REMAJA DI SMAN 3 TAMBUSAI KABUPATEN ROKAN HULU - heny sepduwiana; Fitria Sari; Herawati, Rika; Andria (Fakultas Ilmu Kesehatan, 2024)
HIV/AIDS is a disease that is very feared, because until now there has been no cure, so it can be said that people affected by this disease do not have a long life expectancy. The phenomenon of people living with HIV/AIDS tends to increase in both developed and developing countries, including Indonesia. Several studies in Indonesia show that people with HIV/AIDS are not only found in big cities on the island of Java, but also on other islands, even in small towns. The purpose of this study was to determine the effect of HIV/AIDS counseling on adolescent knowledge in students of SMAN 3 Tambusai, Rokan Hulu Regency. This research method uses a preâ‚‹experimental research method using a one group pretestâ‚‹posttest design, a study conducted with one group given a certain treatment, then observed before and after counseling. The results of the study showed that there was an effect of giving counseling. It was obtained from research on the knowledge of adolescents before counseling was carried out with an average value of 10.53 with an SD of 2.124 and after counseling with an average value of 16.18 with an SD of 1.647. The difference in the average knowledge of adolescents before (pretest) and after (posttest) counseling was carried out was 5.650 based on the statistical test results obtained p value = 0.0001, which means the value (p <0.05). The research results show that there is a significant relationship between counseling and adolescent knowledge. The conclusions and suggestions that can be given are that counseling is very effective in increasing the knowledge of adolescents at SMAN 3 Tambusai about HIV/AIDS. Keywords: Counseling, Knowledge, HIV/AIDS, SMAN 3 Tambusai 2023